(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to examine the impact of accounting conservatism on earnings volatility and the quality of accounting information under fair value measurement, as applied on to Qatar National Bank and Qatar Islamic Bank. The study adopts a quantitative approach using linear regression models to test the hypotheses. Accounting conservatism is used as the independent variable, while earnings volatility, fair value measurements (OCI) and accruals are treated as the dependent variables. The findings reveal a divergence between the two banks, that is accounting conservatism does not have a significant effect on earnings volatility in QNB, whereas it shows a positive and statistically significant effect in QIB, particularly at higher levels of fair value measurement. On the other hand, accounting conservatism has a positive and significant impact on the quality of accounting information in both banks, with a stronger effect observed in QIB. The study concludes that accounting conservatism is an effective mechanism for enhancing the quality of accounting information; however, its effect on earnings volatility varies depending on the characteristics and asset structure of each bank. The study recommends strengthening the application of accounting conservatism and improving fair value disclosure practices to enhance financial reporting quality and reduce volatility-related risks.